RECONSTRUCTING THE AUTHOR’S VOICE IN TRANSLATION: A STYLISTIC APPROACH TO LITERARY EQUIVALENCE - Dilnoza Kurbanbayeva Sheripbay qizi (World Scientific Research Journal, 2025)
Abstract: In Translation, the issue of restoring the author's voice becomes important within the framework of literary equivalence. In the process of translation, the author's unique style, methods of expression and artistic images should be preserved, and the spirit and meaning of the original text should be fully conveyed to the reader. This requires an approach to restoring the author's voice, both artistically and aesthetically, rather than giving the translation only literal meaning. The concept of literary equivalence is considered, in principle, as one of the main criteria that determine the quality of translation. It serves to ensure that the translation matches the original text in content, style and aesthetics. And restoring the author's voice in translation is one of the main directions for ensuring this equivalence.